Academic Performance of Native and Immigrant Students: A Study Focused on the Perception of Family Support and Control, School Satisfaction, and Learning Environment - Santos, Miguel A.; Godás, Agustín; Ferraces, María J.; Lorenzo, Mar (Frontiers in Psychology, 2016)
The international assessment studies of key competences, such as the PISA report of the OECD, have revealed that the academic performance of Spanish students is significantly below the OECD average; in addition, it has also been confirmed that the results of immigrant students are consistently lower than those of their native counterparts. Given the context, the first objective of this work is to observe the variables (support, control, school satisfaction and learning environment) which distinguish between native and immigrant students with high and low academic performance; the second objective is to check, by comparing the native and immigrant students with high and low performance and separating the two levels, to find out which of the selected variables clearly differentiate the two groups. To this end, a sample of 1359 students was used (79.8% native students and 20.2% immigrant students of Latin American origin), who were enrolled in the 5th and 6th year of Primary Education (aged 10-11 years) and in the 1st and 2nd year of Secondary Education (aged 12-13 years). The origin and the fact of being a retained student or not were estimated as independent variables, whereas their responses to the variables of perceived family support and control (paternal and maternal separately), their school satisfaction and assessment of the learning environment were taken into account as dependent variables. Considering that the reliability of the scales used is adequate, along with the optimal factorization in a series of coherent constructs, it was revealed that the main differences consisted of individual dimensions (perception of family support and control) and, to a lesser extent, of dimensions related to the context (assessment of the school and learning environments). Given the results obtained, our intention is to provide solid evidence that would facilitate the design of family involvement programs, helping to improve students' educational performance.